Opportunistic Recording of Live Experiences Using Multiple Mobile Devices - Cunha, Bruna C. R.; Uscamayta, Andrey Omar M.; Pimentel, Maria da Graça Campos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
In this work, we present a case study in which participants used a mobile application for collaborative record presentations. We developed an application for Android-enabled devices to investigate the usability and design requirements of a mobile and collaborative capture system. Our main concern is to facilitate collaboration and create an enhanced result without adding complexity in relation to the individual capture task. In this way, we focused on problems related to the usability and to the awareness information that enables users to conduct an opportunistic recording. We report our case study results and discuss design requirements we identified for the collaborative recording of presentations by users in possession of smartphones and tablets.